Understanding the Pathophysiology of Diabetic Retinopathy for Early Screening. (CIPEEX, 2025)
Diabetic retinopathy (DR) is a microangiopathy resulting from the chronic effects of diabetes mellitus (DM), with an estimated prevalence of 24 to 39% in diabetic patients in Brazil. DR is one of the leading causes of vision loss in individuals between the ages of 20 and 75, which may be aggravated by associated complications such as dyslipidemia, hyperglycemia, and hypertension. The aim of this study was to understand the pathophysiology of DR and the importance of early screening. The study used data from articles published in the last five years, selected from the PubMed, SCIELO, and LILACS databases, which addressed the relationship between the pathophysiology of DR and the need for early screening. After a literature review, four relevant articles were included in the analysis. The results highlight that DR progresses from increased vascular permeability, which causes microaneurysms, to retinal ischemia, with signs such as cotton wool spots and neovascularization in advanced stages. The current classification of DR includes Non-Proliferative Diabetic Retinopathy (NPDR), subdivided into mild, moderate, and severe, and Proliferative Diabetic Retinopathy (PDR). Diabetic macular edema (DME) may occur at any stage of DR. The conclusion emphasizes the severity of DR, its pathophysiological complications, and the importance of early screening and treatment to reduce its consequences. Management of risk factors, such as dyslipidemia and hypertension, is essential to prevent disease progression and its implications for patients' quality of life.
Keywords: diabetic retinopathy; physiopathology; diabetes complications